Ventricular Arrhythmia in Septal and Apical Hypertrophic Cardiomyopathy: The French-Canadian Experience - Steinberg, Christian; Nadeau-Routhier, Charles; André, Philippe; Philippon, François; Sarrazin, Jean-François; Nault, Isabelle; O'Hara, Gilles; Blier, Louis; Molin, Franck; Plourde, Benoit; Roy, Karine; Larose, Eric; et al. (Frontiers in Cardiovascular Medicine, 2020)
Background: Apical hypertrophic cardiomyopathy (aHCM) is thought to have a more benign clinical course compared to septal HCM (sHCM) but most data have been derived from Asian cohorts. Comparative data on clinical outcome in Caucasian aHCM cohorts are scarce and the results are conflicting. The aim of this study was to estimate the prevalence and outcome of aHCM in French-Canadians of Caucasian descent. Methods and results: We conducted a retrospective, single center cohort study. The primary endpoint was a composite of documented sustained ventricular arrhythmia (VA), appropriate ICD-therapy, arrhythmogenic syncope, cardiac arrest or all-cause mortality. A total of 301 HCM patients (65% males) were enrolled including 80/301 (27%) with aHCM and 221/301 (73%) with sHCM. Maximal wall thickness was similar in both groups. Left ventricular apical aneurysm was significantly more common in aHCM (10% vs 0.5%;p<0.001). The proportion of patients with myocardial fibrosis ≥ 15% of the left ventricular mass was similar between aHCM and sHCM (21% vs 24%;p=0.68). Secondary prevention ICDs were more often implanted in aHCM patients (16% vs 7%; p=0.02). The primary endpoint occurred in 26% of aHCM and 10.4% of sHCM patients (p=0.001) and was driven by an increased incidence of sustained VA (10% vs 2.3%;p=0.01). Multivariate analysis identified apical aneurysm and a phenotype of aHCM as independent predictors of the primary endpoint and the occurrence of sustained ventricular tachycardia. Unexplained syncope and a family history of sudden cardiac death were additional predictors for sustained VA. Apical HCM was associated with an increased risk of ventricular arrhythmia even when excluding patients with apical aneurysm. Conclusions: The phenotype of apical HCM is much more common in French-Canadians (27%) of Caucasian descent compared to other Caucasian HCM populations. Apical HCM in French-Canadians is associated with an increased risk for ventricular arrhythmia.